A performance study of a wearable balance assistance device consisting of scissored-pair control moment gyroscopes and a two-axis inclination sensor - Romtrairat, Parineak; Virulsri, Chanyaphan; Wattanasiri, Panipat; Tangpornprasert, Pairat (Journal of biomechanics, 2020)
Excessive postural sway while standing can lead to falls and injuries. A designed wearable balance assistance device which consists of scissored-pair control moment gyroscopes and a two-axis inclination sensor is introduced to reduce fall risk from excessive sway among the elderly. The prototype has dimensions of H50cm × W44cm × D30cm and weighs 15.03 kg. This study aims to investigate the effects of generated torque of the prototype on human subjects and aims to determine if the two-axis inclination sensor can detect sway amplitude and sway direction during an occurrence of excessive sway. Two healthy male subjects participated in the study. According to the results, the detected body incline angle related to the acquired sway amplitude of COP trajectories with correlation factors of 0.92 and 0.88 for the two subjects. The detected sway angle related to the acquired sway direction of COP trajectories with the correlation factors of 0.99 and 0.98 for the two subjects. The maximum-allowable generated torque of the prototype with an assigned actuating angle varying within ±15.6° from the acquired sway direction of COP trajectories was able to drive the COP of 60-kilogram-weighted healthy subject maintaining balance at posterolateral limits of stability with an average body incline angle of 5.74° to pass his standing secure zone. The results indicate that the prototype has the potential of being a wearable balance assistance device which can reduce fall risk from excessive sway among the elderly; however, some improvements are still required in regards to shape, size, mass, generated torque, and strength.